Participation and Public's Expectations for Mliwang Metu Banyune as A Village Tourism Development Program - Muhamad, Muhamad; Santoso, Djarot Heru; Arifin, Arifin (E-Journal of Tourism; Volume 11 Number 1 (March 2024), 2024)
The study aims to examine the public's participation and expectations regarding the contribution of industry to the development and ongoing upkeep of Mliwang, as a tourist destination. "Mliwang Metu Banyune" is the program that Bangun Indonesia Solutions Company (SBI) uses to encourage community development. This has a significant impact on expectations from society and their participation. The goal of this study is to evaluate the Bangun Indonesia Solutions Company's (SBI) program. The developed method is a quantitative descriptive method. This technique is employed to gauge public expectations for the Mliwang Metu Banyune Program as well as participation levels. The study's sample consists of sixty respondents from the community. The study's findings indicate that the public has very high expectations for the ongoing activities and is actively participating in them.